ANALYSIS OF STUDENT'S MATHEMATIC CONNECTION BASED ON MATHEMATICS ABILITY (Universitas PGRI Sumatera Barat, 2021)
One of the components that need to be developed to train students to think better is to develop the ability of students to connect the problems obtained not only in mathematics material or in the application of daily life, students must also be able to connect with other sciences related to mathematics, this is called mathematical connection. This ability can be known after students complete a written connection ability test, the questions used are short story questions about quadratic equations. The subjects taken were students with high, medium and low abilities from class XI MA Al-Ihsan students. The researcher uses descriptive qualitative to support this research. Subjects were given a connection test and analyzed to determine the consistency of the subject's answers using time triangulation and paying attention to mathematical connection indicators. Interviews were used to complete the subject's answers when they were not written and to clarify the connection results of each subject. The results of the study show that subjects with high abilities can meet all three existing indicators, for moderate subjects only get two indicators and low only relate to mathematical material so that only one indicator is met.